Changes in haemodynamics during single lung transplantation under venovenous extracorporeal membrane oxygenation. (21st April 2022) - Oishi, Hisashi; Matsuda, Yasushi; Ejima, Yutaka; Toyama, Hiroaki; Hirama, Takashi; Watanabe, Tatsuaki; Watanabe, Yui; Niikawa, Hiromichi; Noda, Masafumi; Okada, Yoshinori
Abstract: OBJECTIVES: The objective of the present study was to examine the effect of venovenous (VV) extracorporeal membrane oxygenation (ECMO) use on the haemodynamics during single lung transplantation (SLT) and postoperative course. METHODS: Forty-seven patients who underwent SLT for end-stage lung diseases in our lung transplant centre between January 2010 and December 2019 were included in this study. The recipients were divided into 3 groups according to the type of intraoperative ECMO. No type of ECMO was intra-operatively used in the patients of the no use of ECMO (NO ECMO) group. The patients in the venoarterial (VA) and VV ECMO groups were put on VA and VV ECMO during the surgery, respectively. The data were compared among the 3 groups. RESULTS: There were 13 SLT cases in the NO ECMO group, 23 SLT cases in the VA ECMO group and 11 SLT cases in the VV ECMO group. Re-exploration for bleeding was performed in 3 (13.0%) recipients in the VA ECMO group. No recipients required re-exploration in the other groups. In the NO ECMO group, systolic pulmonary arterial pressure (PAP) was significantly elevated during the main pulmonary artery clamp on the SLT side and it was decreased in the VA ECMO group because of the bypass flow. Interestingly, systolic PAP was significantly decreased in the VV ECMO group as well. CONCLUSIONS: VV ECMO decreases the PAP during SLT, which could be a choice for extracorporeal life support during lung transplant surgery for patients, even those with pulmonary hypertension. Abstract : Lung transplantation is now an established treatment for patients with end-stage lung diseases.